2017
DOI: 10.1515/ijamh-2016-0138
|View full text |Cite
|
Sign up to set email alerts
|

Differences in physical activity, eating habits and risk of obesity among Kuwaiti adolescent boys and girls: a population-based study

Abstract: The study aimed to assess gender differences among Kuwaiti adolescents in healthy living choices that impact the risk of obesity. A cross-sectional multistage cluster design was employed with a representative sample of 2672 students aged 13-15 years who completed a self-administered Global School-based Student Health (GSHS) survey. The study found that around 48.0% of adolescents were overweight and obese. More boys than girls were obese (28.2% vs. 22.3%, p < 0.0001). However, boys were more likely than girls … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 25 publications
5
23
0
1
Order By: Relevance
“…Both behaviours are likely associated with overweight and obesity [29,30]. Consistent with the literature [31][32][33][34], this research found skipping breakfast was common among participants. It was noticed that the rate of skipping breakfast remained consistent, with a slight increase during the pandemic.…”
Section: Discussionsupporting
confidence: 87%
“…Both behaviours are likely associated with overweight and obesity [29,30]. Consistent with the literature [31][32][33][34], this research found skipping breakfast was common among participants. It was noticed that the rate of skipping breakfast remained consistent, with a slight increase during the pandemic.…”
Section: Discussionsupporting
confidence: 87%
“…The latter aspect is of special interest in the specific analysis of girls, who showed significantly more sedentary patterns than boys throughout the entire study period of twenty years. This phenomenon is a constant finding in similar studies, where girls always show less active lifestyles than boys of the same age [39,44].…”
Section: Discussionsupporting
confidence: 65%
“…The results from this study can serve as a guiding tool for shaping health strategy during this pandemic by health authorities. As Gulf countries grew enormously in wealth, living standards were raised, albeit at a cost of more sedentary and comfortable life routine [5,13,14]. Kuwait had previously developed a 'Kuwait National Programme for Healthy Living (2013-2017)' [15], authorities can develop a strategic plan to counter harmful effects of this pandemic on health that are originating from sedentary lifestyle, unhealthy eating patterns and psychological issues.…”
Section: Characteristics Of Respondentsmentioning
confidence: 99%
“…This poor lifestyle can be detrimental to the health structure of middle eastern countries especially Kuwait, where obesity has a high prevalence among people of Gulf countries, where a huge proportion of Kuwaiti national meet the World Health Organization's de nition of 'obesity' [4]. According to Al-Nohair, the prevalence of obesity among Kuwaiti males is 36% and females is 48% [4,5]. This high rate of obesity in Kuwait has been attributed to a plethora of biopsychosocial risk factors and a polygenic etiology [4].…”
Section: Introductionmentioning
confidence: 99%